«Host-guest» complexing of double-walled carbon nanotube with metallocenes - O. V. Mykhailenko (Хімія, фізика та технологія поверхні)
Complex compounds of various types and nature have been widely applied in many fields of science and technology. Complex aggregates based on nanostructures such as nanotubes and other coordination compounds, for example, metallocenes, have unique properties, since a combination of their individual characteristics provides for further growing interest to the research in chemistry, physics, electronics, medicine, etc. The initial structure was a (5.5)@(10.10) nanotube (CNT) having 270 carbon atoms. Intercalation of this double-walled carbon nanotubes (DWCNT) assumes placing the intercalate inside the (5.5) CNT, into intertubular space, and its differently oriented sorption on the outer surface of the (10.10) CNT. By employing the methods of MM+, РМ3 and Monte-Carlo, the positioning has been studied of molecules of tricarbonyl(cyclopentadienyl)manganese, monocyclopentadienylferrum(ІІ), bis(cyclopentadienyl)nickel and bis(?5-cyclopentadienyl)cobalt in a double-walled (5,5)@(10,10) carbon nanotube depending on intercalate concentration and intercalation temperature. The temperature increase (over ~455–460 K) causes gradual bond ruining followed by extrusion of interwall intercalate. Further temperature increase up to 620–650 K is characterised with intercalate external surface desorption, stabilising the whole systems and keeping the interwall intercalate only. It is necessary to note that the suggested model variant allows to demonstrate the thermodynamic selectivity of physical and chemical sorption-desorption. At lower temperatures there appears physical sorption, its natural feature is most likely to overlap the non-hybridized orbital 3dxy of the metal ions with the ?-system of the DWCNT side surface while chemisorption is observed at higher temperatures that is peculiar or ?-? interactions of aromatic and quasiaromatic cyclic (heterocyclic) systems. Moreover, simultaneous presence of donor/acceptor feature of the DWCNT’s intertube space as a result of positive and negative Gaussian curvature, makes it possible to regulate orientation of intercalate donor and acceptor edges what allows us to view it as a potential molecular switch. There have been calculated the UV-spectra for (5,5)@(10,10) DWCNT depending on the intercalate concentration as well as an association constant of the systems which makes 26.45 l·mol–1 (for system with ferrocene); 36.2 l·mol–1 (for system with nickelocene); 76.8 l·mol–1 (for system with cobaltocene) and 6.745 l·mol–1 (for system with manganocene).